Evaluation of the efficacy of bacteriophages against Staphylococcus aureus - Tan, Cheng Siang; Nurul Aqilah, Binti Aqiludeen; SIti Fairouz, Binti Ibrahim; Ruixin, Tan; Gowbei, Annabel; Mijen, Alexander Beemer; Santhana, Raj L. (2017)
Staphylococcus aureus (S. aureus) is an opportunistic human pathogen that has the ability to cause both health care-associated and community-acquired infections (Chambers, 2001). The infections were once, easily treated with antibiotics before resistance against beta-lactams (eg. Methicillin) and glycopeptides (eg. Vancomycin) began to emerge over the years and caused an increase in mortality and morbidity rates in patients infected with S. aureus (Boucher & Corey, 2008, Howe et al., 1998). This has led to an increased interest in the exploration of the use of bacteriophages as a way to combat multi-drug resistant organisms because bacteriophages has bacteriolytic mechanism independent from those of any known antibiotics (Matsuzaki et al., 2005).